HIV-infected physicians: how best to protect the public? - Karrel, A I (1995)
The debate about public safety as it relates to physicians living with HIV infection concerns all Canadians. A review of the evidence strongly suggests that the best way to protect the public is by strict adherence to universal precautions and the voluntary use of expert advisory panels on an anonymous basis. Mandatory reporting of the identities of HIV-positive physicians and the use of expert panels that have the authority to ban doctors from doing certain procedures would only lead to fewer doctors at risk for HIV infection coming forward for testing and treatment and to mandatory testing for all.